RETRACTED: The perceived service quality in higher education: An empirical study using the SERVPERF dimensions - Fuchs, Kevin; Fangpong, Keerati; Southam, Ashleigh (Frontiers in Education, 2022)
Students have become more concerned about their university selection and are more demanding of the universities they chose. In this highly competitive environment, universities need to understand these expectations. This study examines how undergraduate students perceived the service quality in their higher education institution. To answer that question, a questionnaire was developed and was distributed amongst tourism and hospitality students in Thailand. A variety of statistical techniques was used to analyze the 208 eligible responses. The results revealed that year of study is a significant factor on students reported levels of service quality, whereas gender and nationality were not. This study emphasizes the need to consider the student’s year of study (e.g. age) when policymakers and educators evaluate students’ needs in undergraduate tourism education. The article concludes by presenting implications for educators, policymakers, and education researchers.